Sim ou não : a luta política pela emancipação do município de Marau e as disputas pelo poder - Aguirre, Eliane (2008)
This study presents an approach of the political disputes which happened in the city of Marau and which were verified during the movement for emancipation it, between 1945 and 1955, and subsequent to that period. However, the temporary delimitation that begins with the end of the New State extends until the 1980 s, in the period to democratize again, after the end of the military dictatorship, in the beginning of the political opening. This paper also approaches the presence of the Catholic Church in the local political disputes, as well as the ethnic characteristic of the place certain for the Italian descendants presence. Another topic in the present study concerns the politicians local collisions verified in the period of the military dictatorship, especially in the one regarding to the legislatures which happened after the emancipation politician administrative. Based on that context, the aim is to show the dispute for the local political power, once PSD consisted then of the largest electoral force in the district of Marau, while PTB is the command of Passo Fundo city hall. Therefore, in the conquest for the municipal autonomy of Marau, different political actors have pronounced in the most ways, revealing that the political game extrapolates the traditional dimensions, embracing the society in all complexity that composes it.